Viabilidad de medir campos magnéticos externos mediante espectroscopía de polarización del átomo de Cesio (2022)
The objective of this work is to study the feasibility of measuring magnetic fields from the polarization spectroscopy method in cesium atoms. To fulfill the proposed objective, a simulation of the polarization spectroscopy signal of the D2 line of the 133Cs atom was performed and an experimental setup was implemented to record a signal for the same case. To the implemented experimental setup was added a set of three-axis Helmholtz coils generating different magnetic fields (Bz) on the 133Cs sample. For each field (Bz) a polarization spectroscopy signal was taken and the total of the signals was used to determine the feasibility of using the shape of a given signal to estimate (Bz). It was observed that there are two parameters sensitive to magnetic field variations (Bz) that can be obtained from a signal. The first is the resonance frequency for the transition between the Zeeman sublevels |6^2 S_{1/2},4,4> and |6^2 P_{3/2}, 5, 5>. In this case, the splitting of the levels due to the Zeeman Effect is proportional to the magnetic field present following the following constant of proportionality: dv4-->v5(Bz)/dBz = (1,945 ± 0,007) MHz/G. The second parameter is the signal amplitude for the case where the laser frequency is kept in resonance with the frequency of some transition before the splitting, i.e., for a magnetic field Bz = 0. In the latter case, the 133Cs atoms must be optically pumped with a circularly polarized beam of light (¿+) whose frequency is resonant with the transition (6^2 S_{1/2}, F = 4) --> (6^2 P_{3/2}, F = 5). This generates an anisotropy of the medium that can be associated with the Macaluso-Corbino Effect (resonant version of the Faraday Effect). Under this scenario, the value of Verdet's constant (V) of 133Cs was arrived at as V = (99 ± 40) rad/(T · m), this value is comparable to those reported for other magneto-optically active materials. From the results, a scheme for measuring magnetic fields in real-time and another for the creation of ultra-stable lasers of controllable frequency are proposed.